A multi-layer integrated thermal protection system with C/SiC composite and Ti alloy lattice sandwich. (15th December 2019) - Xu, Yingjie; Xu, Ningxin; Zhang, Weihong; Zhu, Jihong
Abstract: In this paper, a multi-layer integrated thermal protection system (ITPS) is proposed and compared with two existed ITPS. This multi-layer ITPS consists of a carbon fiber reinforced silicon carbide matrix composite (C/SiC) panel, a glass wool layer and a titanium (Ti) lattice sandwich filled with glass wool. In order to satisfy the aerodynamic shape requirement of hypersonic vehicles, a curved ITPS structure is concerned in this study. Multi-layer curved ITPS and single-layer curved ITPS made of Ti alloy and C/SiC composite are firstly analyzed and discussed under typical aerodynamic heating and pressure loads. Numerical results show that the proposed multi-layer ITPS provides efficient thermal insulation and load bearing properties compared with the C/SiC sandwich ITPS and Ti alloy sandwich ITPS. Secondly, multi-layer curved ITPS samples are fabricated. Experimental tests and numerical validation are carried out to evaluate the heat transfer characteristics of the ITPS samples.